High-beta-glucan and low-glycemic index functional bulgur produced from high-beta-glucan barley - Zeynep Hazal Tekin-Cakmak; Cagla Ozer; Kubra Ozkan; Halide Yildirim; Francesco Sestili; Abderrazek Jilal; Osman Sagdic; Muhammet Ozgolet; Hamit Koksel (Journal of Functional Foods, 2024)
A high β-glucan hull-less barley (cv. Chifaa) was used in bulgur production and its technological and nutritional properties were compared with bulgurs of another hull-less barley and durum wheat. Although Chifaa bulgur had longer cooking time (9.5 min) which is expected to have an increasing effect on total organic matter (TOM), it had lower TOM (1.31 g/100 g) than the durum bulgur. The phenolics of barleys were significantly higher than those of Kiziltan wheat. The amounts of total phenolic contents decreased after bulgur production. While glycemic index (GI) of durum bulgur was high, GI of barley bulgurs were medium probably due to their higher β-glucan contents. The GI of Chifaa (56.25) is very close to the limit value of low GI foods (56). The limit to bear the health claim is 3 g of β-glucans/serving. The results indicated that this can be provided per serving of high β-glucan barley bulgur.